Interprofessional Collaboration Competencies in the Health System: A Systematic Review - Fatemeh Vaseghi; Mohammad Hossein Yarmohammadian; Ahmadreza Raeisi (Wolters Kluwer Medknow Publications, 2022)
Background: Today's health systems require the collaboration of diverse staff such as physicians, nurses, social workers, and other healthcare professionals. In addition to professional competencies, they also need to acquire interprofessional competencies. Effective interprofessional collaboration among healthcare professionals is one of the solutions that can promote the effectiveness of the health system using existing resources. Materials and methods: A systematic review was conducted in 2021 according to the PRISMA and through searching Web of Science, Scopus, PubMed, ProQuest, Science Direct, Emerald, Springer Link, Google Scholar, SID, and Magiran databases. The official websites of WHO, United Nations, and World Bank were also searched. The time frame for the research was from 2010 to 2020, and included both the English and Persian languages. Out of 7267 initially retrieved articles, 17 articles finally met the quality evaluation criteria and were analyzed through qualitative content analysis. Then their full texts were retrieved and analyzed in MAXQDA software, and final results were categorized. Results: Competencies have been explored in various areas of health care, especially in the clinical field. The competencies introduced were extracted and categorized into six domains of "patient-centered care," "interprofessional communication," "participatory leadership," "conflict resolution," "transparency of duties and responsibilities," and "teamwork." The competence of "transparency of duties and responsibilities" was mentioned in all studies and is required for any collaboration. Conclusions: Interprofessional competencies provide quality, safety, and patient-centeredness through effective collaboration. Integrating interprofessional competencies into the educational curriculum, in-service training, and continue education is essential to form effective interprofessional collaboration.